Failure of cellulolysis in the rumen of reindeer fed timothy silage - Olsen, Monica A.; Aagnes, Tove H.; Mathiesen, Svein D. (Rangifer, 1995)
Three male reindeer (Rangifer tarandus tarandus) calves were brought from mountain pastures in April and fed regrowth timothy (Phleum pratense) silage with 76% leaves and 24.0% dry matter (DM) ad libitum. The silage contained (on DM basis) 25.4% cellulose, 12.0% crude protein and 19-6% water soluble carbohydrates. After an initial period of 11 days the daily silage intake rose to almost similar values for all animals, but independently of food intake, body mass (BM) increased by as much as 13.3 kg for animal R3 during the first 21 days, compared to 4.4 kg and 2.8 kg for Rl and R2, respectively. At slaughter the wet weight of the rumen contents of animal R3 constituted 30.2% of the total BM, compared to 18.5% and 19.1% in animals Rl and R2, respectively. A reduced ability of the rumen micro-biota to ferment pure cellulose in vitro was observed in R3. The ruminal pH was 7.07 and the concentration of volatile fatty acids was only 50.0 mM in R3, indicating a low rate of fermentation. The initial rates of in vitro dry matter digestibility of timothy silage and standard hay were also affected by the rumen fermentation failure in animal R3. Depressed rumen cellulolysis, which may be related to natural periods of starvation prior to the feeding experiment, could have caused the low rate of fermentation and the large rumen size observed in this animal.